2018
DOI: 10.3390/en11102725
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Learning Machines for Solar Photovoltaic Power Predictions

Abstract: The unpredictability of intermittent renewable energy (RE) sources (solar and wind) constitutes reliability challenges for utilities whose goal is to match electricity supply to consumer demands across centralized grid networks. Thus, balancing the variable and increasing power inputs from plants with intermittent energy sources becomes a fundamental issue for transmission system operators. As a result, forecasting techniques have obtained paramount importance. This work aims at exploiting the simplicity, fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…Despite this novel research conducted using different hybrid AI models for estimating global solar radiation, there is still room for the improvement of these techniques [34]. Although employing a numerical weather model's estimation to feed machine learning techniques in global solar radiation estimation can enhance model accuracy, this approach has been applied for wind speed estimation [32].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this novel research conducted using different hybrid AI models for estimating global solar radiation, there is still room for the improvement of these techniques [34]. Although employing a numerical weather model's estimation to feed machine learning techniques in global solar radiation estimation can enhance model accuracy, this approach has been applied for wind speed estimation [32].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that different steps are carried out a priori to process/correct the available dataset to effectively use it for the prediction task (Al-Dahidi et al, 2018;Alomari et al, 2018a;Das et al, 2018). For example, solar radiation and associated power production values are shown to be negative and missing in early and late days' hours, respectively.…”
Section: Asu Weather Stationmentioning
confidence: 99%
“…In practice, to further enhance the prediction performance of the ANN, additional neurons are added to the input (b h ) and hidden (b o ) layers which have a value of 1 (or other constant) for shifting the output of the activation functions left or right to assure that the weights' variations is sufficient to enhance the ANN prediction performance (Abuella and Chowdhury, 2015); • − → β h is the weights vector of the connections that connect the output of each h-th neuron to the output node, and • G 1 () and G 2 () are the hidden and output neuron activation functions, respectively. The former is usually a continuous non-polynomial function, whereas the latter is typically a linear function (Al-Dahidi et al, 2018). The "Log-Sigmoid" has been employed as a neuron activation function following an exhaustive search procedure carried out in Al-Dahidi et al (2018) on the same dataset of the ASU solar PV system.…”
Section: Solar Pv Power Prediction Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Kouz et al [13] proposed a computational model to investigate the effects of dust and temperature on the performance of a photovoltaic system using Artificial Neural Network (ANN) [14] and Extreme Learning Machine (ELM) [15] models. They found that the optimized model predicts a conversion efficiency yielding an R 2 of 91.4%.…”
Section: Introductionmentioning
confidence: 99%